Ethnomedical Practices and Indigenous Household Remedies Used by the Tribals and Rurals of the Bastar Region (Chhattisgarh) - Banik, Ajay; Nema, Sharad (Indian Forester, 2014)
Identification and Documentation of plant diversity used by the tribal’s of Bastar region for Ethnomedicinal practices and indigenous remedies was studied during the year 2012. A total of 103 ethnomedicinal plant species belonging to 50 families were used traditionally to cure various diseases/ailments by the tribal’s. Various parts of these species were used to cure cough, cold, fever, skin diseases, stomach problems, healing wounds, etc. Such studies would help in developing a comprehensive database used in the traditional medicinal practices, strengthening the health care system in the villages and also conserving the traditional knowledge of Tribal’s of Bastar region in Chhattisgarh state. The scientific names, local names and family names of these plant species, along with the parts used and the mode of usage are enumerated.